2002
DOI: 10.1002/arch.10017
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and tissue distribution of cholesterol in Manduca sexta

Abstract: In Manduca sexta larvae, radioactive free cholesterol is absorbed directly from the midgut into mucosal cells where it is stored both in the free form (87% in males and 93% in females) and esterified form (13% in males and 7% in females). Subsequently, cholesterol is transported to fat body via lipophorin in the hemolymph exclusively in the free form. In fat body, the distribution of cholesterol between the free and esterified form varied significantly between genders and developmental stages. Except for the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
5
26
0
Order By: Relevance
“…Great advances have been made in understanding vascular lipoprotein cholesterol transport, and only a few proteins are known to be involved in cholesterol transport and metablism, such as the haemolymph lipophorin (Soulages and Brenner 1991;Jouni et al 2002) and lipoprotein (Bianchi and Capurro 1991). However, intracellular cholesterol trafficking is only beginning to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Great advances have been made in understanding vascular lipoprotein cholesterol transport, and only a few proteins are known to be involved in cholesterol transport and metablism, such as the haemolymph lipophorin (Soulages and Brenner 1991;Jouni et al 2002) and lipoprotein (Bianchi and Capurro 1991). However, intracellular cholesterol trafficking is only beginning to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…(2)]. In the more versatile insect system, the same basic Lp particle carries a wide variety of lipids and selectively delivers specific lipids to specific tissues, e.g., cholesterol to oocytes (13,27) and fat body (27), hydrocarbons to the cuticle (7), and carotenoids to the cuticle or the silk gland, etc. (28).…”
Section: Discussionmentioning
confidence: 99%
“…Processing of dietary phytosterols will involve both assimilation and metabolic de-alkylation, both of which can vary (Knauer et al, 1999;Harvey et al, 1987;Teshima, 1971). Cholesterol and phytosterols are taken up directly by midgut cells in insects (Canovoso et al, 2001;Jouni et al, 2002) and dealkylation of phytosterols then takes place within the midgut cells, rather than in the gut lumen. Sterol assimilation in Calanus helgolandicus is influenced by food concentration, with higher assimilation efficiencies at low food concentrations (Harvey et al, 1987), a pattern also observed by Landry et al (Landry et al, 1984) for carbon and nitrogen assimilation efficiency in C. pacificus.…”
Section: Cholesterol Feeding Growth and Temperaturementioning
confidence: 99%